Ordinance no. 32, An Ordinance Relative to the Prevention of Fires, § 12, YPSILANTI, REVISED CHARTER OF THE CITY (Ypsilantian Publishing House 1898) (Approved 1882). - (:unkn) unknown (General Publisher, 1882)
No person shall fire or set off any squib, crackers, gunpowder or fire works, or fire off any gun or pistol in any street, lane, alley, or other public space, or in any yard, public or private, within the limits of the city, unless by written permission from the Mayor;
--
Keywords: DISCHARGE